Biofilm-Related Infections in Gram-Positive Bacteria and the Potential Role of the Long-Acting Agent Dalbavancin - Oliva, Alessandra; Stefani, Stefania; Venditti, Mario; Di Domenico, Enea Gino (Frontiers in Microbiology, 2021)
Infections caused by Gram-positive bacteria are a major public health problem due to their increasing resistance to antibiotics. Staphylococcus and Enterococcus species' resistance and pathogenicity are enhanced by their ability to form biofilm. The biofilm lifestyle represents a significant obstacle to treatment because bacterial cells result highly recalcitrant to a wide range of antimicrobial compounds normally effective against their planktonic forms. Thus, novel therapeutic strategies targeting biofilms are urgently needed. The lipoglycopeptide dalbavancin is a long-acting agent for treating acute bacterial skin and skin structure infections caused by a broad range of Gram-positive pathogens. Recent studies have shown a promising dalbavancin activity against staphylococcal biofilms, including methicillin-resistant S. aureus (MRSA), methicillin-resistant S. epidermidis (MRSE), and vancomycin-susceptible enterococci. This review outlines the mechanisms regulating biofilm development in Staphylococcus and Enterococcus species and the clinical impact of biofilm-related infections. Besides, it discusses the clinical implications and potential therapeutic perspectives of the long-acting drug dalbavancin against biofilm-forming Gram-positive pathogens.